TRANSFORMASI PENGELOLAAN SAMPAH RUMAH TANGGA : PENDEKATAN ZERO WASTE MENUJU PERUBAHAN PERILAKU BERBASIS LINGKUNGAN - Syifa Rohmah; Jilma Dewi Ayu Ningtyas; Ulfa Kurniasih (CV. Denasya Smart Publisher, 2025)
The problem of household waste management is one of the pressing environmental issues in various countries, including Indonesia. The high volume of waste that is not properly processed contributes to environmental pollution, such as soil, water, and air pollution. Tasik Rejo Village is one of the villages that focuses on waste management, this village has a BUMDes that is active in waste management but is only piled up at the TPS. Through Community Service activities, the service team carries out activities to change waste so that it can be utilized properly. The purpose of this service is to provide education and skills to Tasik Rejo village residents about the importance of maintaining environmental sustainability and a healthy lifestyle through waste processing, one of which is into fertilizer, so that waste can have value that can be utilized. This service method uses the ABCD method where the community plays an active role in every stage. Based on the results of the service, it can be said that the community is not fully aware of the importance of sorting waste, therefore further assistance is needed, but this service activity has a positive influence on changes in healthy living behavior in the community.